An investigation into the shifts in the english translation of judgement in “the general retires and other stories” by Nguyen Huy Thiep - Nguyễn Thị Tường Vi (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Judgement, one of the three systems of Attitude in Appraisal theory which is the realm of ethical and moral assessments of human behavior has been a growing interest for linguists. This thesis aims at examining shifts in the English Translation of Judgement of The General Retires and Other Stories by Nguyen Huy Thiep. The study was conducted based on the framework of Systemic Functional Grammar (SFG) by Halliday (2004), Appraisal theory by Martin & White (2005) and Catford’s Model of translation shift (1965). This descriptive study analyzed the instances of Judgment in terms of semantic features with reference to the Appraisal theory and identified kinds of shift in the translational version using Catford’s Model. The interpretation of the motivation behind the choice of the translator with the shift was done based on knowledge of Transivity, the set of options whereby the speaker encodes his experience of the processes of the external world, and of the internal world of his own consciousness. The analysis of 180 samples of Judgement in the Vietnamese source text (ST) and 115 instances of shift in the English target text (TT) reveals that the distribution of Judgement used in the Vietnamese version show an imbalance in the subcategories of the two systems of Social Esteem and Social Sanction where instances of Judgement of Social Sanction – Propriety and Social Esteem – Capacity show a dominant frequency, in most cases, negative values outnumbered the positive ones. The study also shows that shifts operates at the level of the sentence and its lower constituents where such grammatical components as adjectives and adverbs were used at different positions in ST and TT when the same semantic component of Judgement was expressed in Vietnamese and English where the meaning of permanent/temporary, inherent/non-inherent attribute of the subject of sentence as appraisee of judgement was factored into the shifting.